Effect of Apium graveolens extract on the surface morphology and characteristics of calcium pyrophosphate crystals - SAYAN, PERVİZ; POLAT, SEVGİ (ELSEVIER, 2021)
This aim of the present study was to investigate the crystallization and physical characteristics of the triclinic calcium pyrophosphate dihydrate (t-CPPD) and monoclinic calcium pyrophosphate tetrahydrate ? (m-CPPT ?) crystals created in pure media and in the presence of Apium graveolens extract. The structure, functional groups, crystal morphology, and size of the crystals were investigated experimentally using X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy, atomic force microscopy, and a particle size analyzer. The smaller crystals were created in the presence of the extract media and displayed changes in the t-CPPD crystal shapes from rod like to rounded in addition to rod-like crystals. Zeta potential analyses showed that adding A. graveolens extract resulted in a more negative crystal surface energy (-36.7 ? 1.1 mV) than that in pure media, which was -28.6 ? 1.3 mV. In addition, the thermal decomposition characteristics of the t-CPPD and m-CPPT ? crystals were simultaneously investigated using thermogravimetric analysis combined with FTIR and the main evolved product was determined as H2O. The present study analyzed the structural, morphological, and thermal properties of t-CPPD and m-CPPT ? to provide more comprehensive information on how A. graveolens extract helps prevent the formation of t-CPPD and m-CPPT ? crystals. This information can be an important step in long-term development of an effective therapeutic treatment.
Keywords: B1; Calcium pyrophosphate dihydrate; B1; Calcium pyrophosphate tetrahydrate; A1; Crystal Morphology; B1; Crystallization; B1; Apium graveolens; A1; TGA-FTIR